2010
DOI: 10.5424/sjar/2010082-1216
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of beekeeping wastes for using in seedling production

Abstract: In the present work, different strategies for the utilization of an organic beekeeping waste called «slumgum» were analysed. Slumgum appears in the beeswax-rendering process. A physico-chemical characterization was carried out and the hypothesis that slumgum could be used as nutrient source and growth substrate constituent for seedling production was tested. Analyses revealed that slumgum has an important potential for fertilization: 6.10% N, 0.23% P and 0.4% K, with a total organic matter average content of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Before introducing this topic, it is often important to identify and separate pure beeswax from contaminant resins, such as slumgum, which occur in beeswax samples (Grout 1946;Morales-Corts et al 2010). It was recently reported that waxes and contaminating resins can readily be identified by differential scanning calorimetry (Zhang et al 2012).…”
Section: Discrimination and Classification Of Beeswaxesmentioning
confidence: 99%
“…Before introducing this topic, it is often important to identify and separate pure beeswax from contaminant resins, such as slumgum, which occur in beeswax samples (Grout 1946;Morales-Corts et al 2010). It was recently reported that waxes and contaminating resins can readily be identified by differential scanning calorimetry (Zhang et al 2012).…”
Section: Discrimination and Classification Of Beeswaxesmentioning
confidence: 99%
“…The production of the biochar from honeycomb biomass can partially solve this problem. Moreover, the organics present in this biomass can be the source of heteroatoms (O, N), being the selective active species toward Pt on the surface of the made biochar [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is primarily composed of brood cocoons, moths, larvae of Galleria melonella L., molts, dead bees, bee droppings, pollen, propolis, and small proportions of non-extractable wax, among other elements. Usually, it is stored outdoors and currently has neither has any particular use nor it is recycled (Morales-Corts et al 2010. The worldwide production of slumgum is estimated to 93,000 tons per year (FAOSTAT 2020).…”
Section: Introductionmentioning
confidence: 99%